Blocking the LncRNA MALAT1/miR-224-5p/NLRP3 Axis Inhibits the Hippocampal Inflammatory Response in T2DM With OSA - Du, Ping; Wang, Jiahui; Han, Yelei; Feng, Jing (Frontiers in Cellular Neuroscience, 2020)
Studies have shown that diabetes can cause cognitive dysfunction, and cognitive dysfunction in patients with diabetes combined with obstructive sleep apnoea (OSA) is more severe. LncRNAs are known to be associated with type 2 diabetes mellitus (T2DM) with OSA. This study aimed to investigate the role and underlying mechanism of the lncRNA MALAT1/miR-224-5p/NLRP3 axis in T2DM with OSA. qRT-PCR was used to quantify the expression of MALAT1, miR-224-5p and NLRP3 in brain tissues. NLRP3 expression was assessed by immunohistochemistry (IHC) and immunofluorescent labelling. The interaction involving MALAT1, miR-224-5p and NLRP3 was evaluated by transfection. Western blotting was utilized to evaluate the expression levels of the pathway-related proteins NLRP3, caspase 1, TNFα and IL-1β both in vitro and in vivo. qRT-PCR was used to assess the mRNA expression levels of NLRP3, caspase 1, TNFα and IL-1β both in vitro and in vivo. In brain tissues of T2DM with OSA, MALAT1 and NLRP3 were overexpressed, while miR-224-5p was downregulated, which was consistent with subsequent cell experiments. We screened the miRNAs that could bind to MALAT1 and NLRP3 by the StarBase database and the TargetScanMouse7.2 website. Our research showed that among these miRNAs, the level of miR-224-5p was most significantly negatively correlated with the levels of MALAT1 and NLRP3. In addition, a firefly luciferase assay showed that miR-224-5p, which is a target of MALAT1, directly reduced the expression of the downstream protein NLRP3. Overexpression of miR-224-5p significantly inhibited the expression levels of NLRP3, caspase 1, TNFα and IL-1β in vitro. MALAT1 promoted NLRP3 expression by acting as a competing endogenous RNA and sponging miR-224-5p. MiR-224-5p reduces microglial inflammation activation through the regulation of NLRP3 expression, which ultimately affected the NLRP3/IL-1β pathway in the hippocampus. This suggests that miR-224-5p may serve as a potential target for T2DM and OSA therapy.